2012
DOI: 10.1016/j.bbamem.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel histone-derived antimicrobial peptides use different antimicrobial mechanisms

Abstract: The increase in multidrug resistant bacteria has sparked an interest in the development of novel antibiotics. Antimicrobial peptides (AMPs) that operate by crossing the cell membrane may also have the potential to deliver drugs to intracellular targets. Buforin 2 (BF2) is an AMP that shares sequence identity with a fragment of histone subunit H2A and whose bactericidal mechanism depends on membrane translocation and DNA binding. Previously, novel histone-derived antimicrobial peptides (HDAPs) were designed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…Thus, it has become increasingly important for researchers to reliably determine whether AMPs are able to effectively translocate into bacterial cells (3). Many researchers have turned to confocal microscopy in order to assess cell entry (4)(5)(6)(7)(8)(9)(10)(11). However, bacterial cells are so small that effective imaging is limited by the resolution of conventional light microscopes.…”
mentioning
confidence: 99%
“…Thus, it has become increasingly important for researchers to reliably determine whether AMPs are able to effectively translocate into bacterial cells (3). Many researchers have turned to confocal microscopy in order to assess cell entry (4)(5)(6)(7)(8)(9)(10)(11). However, bacterial cells are so small that effective imaging is limited by the resolution of conventional light microscopes.…”
mentioning
confidence: 99%
“…Overall, the results indicate increased antimicrobial activity of peptides against Gram-negative bacteria than the Gram-positive bacteria. In respect to the peptides, VVY15 peptide produced better activity than the KVL22 peptide which may due to the following reasons: Pavia et al (2012), Lee et al (2007), Thennarasu and Nagaraj (1996) and Zhang et al (1999) reported that the presence of proline in the AMPs decreased the ability of permeabilization, because proline disrupts the ␣-helical structures. In our study also, we observed a proline (P 33 ) residue in the KVL21-synthesized peptide, while proline amino acid is absent in VVY15 peptide.…”
Section: Discussionmentioning
confidence: 92%
“…In this case, MrH4 mRNA received −105.9 kcal/mol as MFE value, hence it is plausible to suggest that the nucleotides of MrH4 mRNA are almost properly paired and only a few nucleotides are left unpaired, thus showing the stability of MrH4 mRNA. According to the available literature (Pavia et al 2012;Torrent et al 2012 KVL22 and VVY15 indicates antimicrobial activity of MrH4 peptides. Moreover, the presence of cationic amino acids including arginine and lysine showed a net positive charge, which is necessary for an AMP (Boman 2003;Nam et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, plasmin activity is generated on the streptococcal surface and involved in invasive spread by degrading fibrin clots, components of the extracellular matrix and antimicrobial peptides [11,14]. It has been shown that plasmin cleaves histones in vitro [15], and it is assumed that histones operate by disintegrating or penetrating the bacterial membrane [16,17]. We therefore speculated that plasminogen acquisition at the streptococcal surface might serve as a survival strategy of GAS in an environment with high local concentrations of extracellular histones.…”
Section: Introductionmentioning
confidence: 99%